PENGARUH KUALITAS PRODUK, PROMOSI, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA E-COMMERCE SHOPEE: Studi Kasus pada Mahasiswa di Jakarta Selatan - Viona Aliadisa (2022)
When many people choosing to shop online, especially during the Covid-19 pandemic, there is a great need for e-commerce with the best quality products, promotions, and brand image. This study aims to prove that there is an effect of product quality on consumer satisfaction, promotion on consumer satisfaction, and brand image on consumer satisfaction. This research is a quantitative research with primary sources of data. The object of this research is students in South Jakarta who use Shopee to shop online. The sample used was 100 respondents, with non propability sampling method especially purposive samppling. Data collection was done through online questionnaries using Google Form. Analytical technique using PLS (Partial Least Square) method with SmartPLS 3.0 application. The results of this research indicate that (1) product quality has a significant influence on customer satisfaction with a coefficient value of 0.493 (2) promotion has a significant influence on customer satisfaction with a coefficient value of 0.421 (3) brand image has no significant influence on customer satisfaction with a coefficient value of -0.007. With the contribution value together with R Square Adjusted 0.730 or there are 73% that affect consumer satisfaction, with 23% influenced by other variables.